Influence of Perceived Value, Variety Seeking, and Promotion on Brand Switching on Fashion Products in E-Commerce (Study on Shopee Customers in Surabaya) - Sari, Putri Anggyelia; Prabowo, Budi (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study was conducted to determine the effect of perceived value, Variety Seeking, and Promotion on Brand switching on Fashion Products in E-Commerce for Shopee customers in the Surabaya area. This type of research is associative research using a quantitative approach. The population in this study are Surabaya people who have made online purchases of fashion products and have experience doing brand switching from one brand of fashion products and to another fashion brand sold in e-commerce. The data collection technique used a questionnaire with a sample size of 100 respondents. The data analysis technique uses multiple linear regression analysis using Statistical Program for Social Science (SPSS) software version 25. The results of this study state that the variables Perceived value (X1), Variety Seeking (X2), and Promotion (X3) simultaneously have a significant effect on Brand switching (Y). Then the variables perceived value and variety seeking partially have a positive and significant effect on brand switching variables, while promotion partially has a negative and significant effect on brand switching variables.